Collective Bargaining through the Magnifying Glass: A Comparison between the Netherlands and Portugal - Alexander Hijzen; Pedro S. Martins; Jante Parlevliet (Institute of Labor Economics (IZA), 2017)
This paper contributes to a deeper understanding of sector-level bargaining systems and their role for labour market performance. We compare two countries with seemingly similar collective bargaining systems, the Netherlands and Portugal, and document a number of features that may affect labour market outcomes, including: i) the scope for flexibility at the firm or worker level within sector-level agreements; ii) the emphasis on representativeness as a criterion for extensions; iii) the effectiveness of coordination across bargaining units; and iv) pro-active government policies to enhance trust and cooperation between the social partners.
Keywords: J5; P52; 330; industrial relations; social dialogue; employment